Manajemen Bandwidth dalam Mengoptimalkan Penggunaan Router Mikrotik terhadap Pelayanan Koneksi Jaringan - Siti Aminah (SAFE-Network, 2022)
The internet with unlimited reach can connect all computers in a connection that makes it easier for users to get information, communicate and establish partnerships. The need for technology is very important to support all existing activities, such as the process of teaching and learning activities, data processing and transactions, administrative needs, exchanging information even in terms of social needs and so on. The problem that often occurs when using the internet is that bandwidth management on the internet is irregular and even wasted, it will even make internet network users experience bandwidth struggles, delays, and lagging. There is a need for bandwidth usage management so that unwanted things don't happen. The purpose of this research will be to apply a Queue Tree method to control clients in providing internet services so that they remain stable and efficient to get test results with QoS (Quality Of Service) parameters in optimizing router use. proxy for network connection services. Where the results obtained from 5 clients and 10 clients by limiting upload and download bandwidth of 50 Mbps on Throughput are 32.08 (%) medium category. The 0.0024 (ms) delay category is very good. Packet Loss 7.4 (%) good category. Jitter of 0.0024 (ms) is very good. And the total result of 10 Client Throughput 17.23 (%) is bad. The delay is 0.0044 (ms) which is great. Packet Loss 4.2 (%) good category. Jitter 0.0044 (ms) is very good by using bandwidth management can optimize internet usage well.